«ШӘРИЯР» ДӘСТАНЫН ОҚЫТЫЎДА ИНТЕРАКТИВ МЕТОДЛАРДАН ПАЙДАЛАНЫЎДЫҢ НӘТИЙЖЕЛИЛИГИ - Алламбергенов, Е.К. (ILIM hám JÁMIYET, 2020)
The article discusses the effectiveness of the use of innovative technologies, including interactive methods in the teaching of literature lessons. The researcher proves with convincing examples that such methods as "corners", "Sinkvein", "IREC" are effective methods of teaching the epic "Shariyar" in an interactive way.
Keywords: «Шәрияр» достони; инновацион технология; интерактив метод; «бурчаклар» методи; синквейн методи; ПСМЖ технологияси; инновацион технология ва натижалилик